Kepuasan Gaji Menjadi Mediator Kunci pada Motivasi Kerja Pegawai - Nasiatul Aisyah Salim; Yosi Mediawati; Claudia Mel Kurniawan; Istiana Faizah Aulia; Leony Talenta Insani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Work motivation is an important factor that contributes to improving employee productivity and organizational performance. One of the factors influencing work motivation is salary satisfaction. Inadequate compensation may reduce job satisfaction, decrease work enthusiasm, and increase employees’ intentions to leave their jobs. This study aims to analyze the relationship between salary satisfaction and employee work motivation. The research employed an analytical observational method with a cross-sectional study design. The study population consisted of employed individuals, including both civil servants and private-sector employees. A total of 197 respondents were selected using the accidental sampling technique. Data were collected through an online questionnaire distributed via Google Forms. The collected data were analyzed using the Spearman Rank correlation test to determine the relationship between salary satisfaction and work motivation. The findings revealed that salary satisfaction has a moderately positive relationship with employee work motivation. Employees who are more satisfied with their salaries tend to demonstrate higher levels of work motivation. These results indicate that compensation plays a significant role in encouraging employees to perform effectively. Therefore, organizations should implement strategies to enhance employee motivation, including the adoption of fair and performance-based compensation systems to support productivity and organizational success